2019
DOI: 10.1001/jamainternmed.2019.0631
|View full text |Cite|
|
Sign up to set email alerts
|

Risk of Hospitalization for Serious Adverse Gastrointestinal Events Associated With Sodium Polystyrene Sulfonate Use in Patients of Advanced Age

Abstract: IMPORTANCE Sodium polystyrene sulfonate is commonly prescribed for the treatment of hyperkalemia. Case reports of intestinal injury after administration of sodium polystyrene sulfonate with sorbitol resulted in a US Food and Drug Administration warning and discontinuation of combined 70% sorbitol-sodium polystyrene sulfonate formulations. There are ongoing concerns about the gastrointestinal (GI) safety of sodium polystyrene sulfonate use. OBJECTIVE To assess the risk of hospitalization for adverse GI events a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
102
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 118 publications
(109 citation statements)
references
References 26 publications
2
102
0
5
Order By: Relevance
“…This finding adds real‐wold evidence to the notion that HK management remains a major unmet need in nephrology practice . Indeed, data on effectiveness, in terms of efficacy and safety, of potassium‐binding agents today available have been scarce and ambiguous despite the long‐standing use …”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…This finding adds real‐wold evidence to the notion that HK management remains a major unmet need in nephrology practice . Indeed, data on effectiveness, in terms of efficacy and safety, of potassium‐binding agents today available have been scarce and ambiguous despite the long‐standing use …”
Section: Discussionmentioning
confidence: 76%
“…8,36 Indeed, data on effectiveness, in terms of efficacy and safety, of potassium-binding agents today available have been scarce and ambiguous despite the long-standing use. [37][38][39][40] The current study is limited to inclusion of costs from the perspective of the NHS in Italy, thus non-medical and indirect costs were not included. The study by Cicchetti and colleagues reports the total costs of dialysis patients in Italy, considering both direct, medical and non-medical, and indirect costs.…”
Section: Subgroup Analysismentioning
confidence: 99%
“…220,231 A subsequent retrospective single-center study of around 125,000 patients found a low incidence rate of colonic necrosis overall that was not significantly different in people who had or had not been exposed to SPS (0.14% in patients who had received SPS and 0.07% in patients who had not received it; relative risk 2.1; 95% CI: 0.7-6.5). 232 In a linked-data cohort study of 28,000 propensity-matched SPS users between 2003 and 2015, outpatient SPS prescription was associated with increased hospitalization for adverse GI events (19 per 10,000 in the 30 days following prescription, compared with 9 per 10,000 in control subjects); 233 this was independently confirmed in a similar administrative cohort. 234 After release of these findings, some have strongly recommended that SPS no longer be used.…”
Section: Chronic Hyperkalemiamentioning
confidence: 86%
“…Furthermore, this K þ -binding agent has been associated with gastrointestinal intolerance and serious gastrointestinal complications. [71][72][73] The US Food and Drug Administration warns against using SPS with sorbitol because of cases of intestinal necrosis and other serious gastrointestinal events (e.g., bleeding, ischemic colitis, and perforation). 74 They also recommend separating the administration of SPS from other oral medicines by $3 hours because of the nonspecific binding properties of SPS.…”
Section: Nondialysis Options For Managing Hyperkalemiamentioning
confidence: 99%